The recent timberline changes in the Tatra Mountains: A case study of the Mengusovská Valley (Slovakia) and the Rybi Potok Valley (Poland) - Kaczka, Ryszard J.; Lempa, Michał; Czajka, Barbara; Janecka, Karolina; Rączkowska, Zofia; Hreško, Juraj; Bugar, Gabriel (IGiPZ PAN, 2015)
A comparison was done of the timberline course from the mid-20th and beginning of 21st century, in Mengusovská Valley (Slovakia) and Rybi Potok Valley (Poland). These are two valleys in the High Tatra Mts. Aerial photosand satellite images were used to assess the changes of the timberline in the two valleys. The course of the timberline ecotone in both valleys is similar. In both valleys, the stable timberline section is almost half of the totaltimberline length. In both valleys there has been an increase in the elevation of the timberline (on average by 10 m in the Mengusovská Valley and 15 m in the Rybi Potok Valley), and free spaces have been increasinglyclosing up. The progressive changes of the timberline are mainly due to the limit placed on human economic activity, and to climate warming. Inactive avalanche paths have led to an enlargement of the forest area in bothvalleys. The reduction of avalanche activity is the direct result of climate warming in the Tatra Mts. and from the decrease in the amount of snow in winters.
24 cm
Keywords: snow avalanches; Carpathians; Tatra Mountains; photointerpretation; reafforestation; timberline ecotone